1990
DOI: 10.1007/bf01281562
|View full text |Cite
|
Sign up to set email alerts
|

Refractories based on fused mullite

Abstract: The production of such nozzles is being introduced at the Krasnoarmeisk factory .Body compositions 4-6 and 62-a were used to make a trial batch of baddeleyite inserts which were fixed into mullite-corundum bases, impregnated with pitch, and tested in the ladles for casting steel into ingot molds, and with continuous casting.Tests confirmed that the inserts with the higher thermal-shock resistance (6 and 62a) during casting of manganese steels from 170-ton ladles at the Donets factory had lower wear. The wear o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This fact was also observed in the spherical granules based on mullite [6]. This fact was also observed in the spherical granules based on mullite [6].…”
supporting
confidence: 75%
“…This fact was also observed in the spherical granules based on mullite [6]. This fact was also observed in the spherical granules based on mullite [6].…”
supporting
confidence: 75%
“…We have shown that it is possible to obtain spheres or granules by blowing jets of molten mullite with compressed air and cooling the molten droplet in air or water medium [5].…”
mentioning
confidence: 99%